Analysis of Shoreline Change along Cape Coast-Sekondi Coast, Ghana. (16th June 2016) - Dadson, Ishmael Yaw; Owusu, Alex Barimah; Adams, Osman
Abstract : The two most important factors constantly impinging on the net movement of shorelines are erosion and accretion. This study analyzed the role of erosion and accretion in shoreline changes along the coast between Cape Coast and Sekondi in the central and western regions of Ghana, respectively. Aerial photographs, satellite images, and topographical maps were used. In addition, field survey using Global Positioning System (GPS) was conducted at selected locations due to the unavailability of satellite image for 2013. Shoreline change analysis was conducted using Digital Shoreline Analysis Systems based on End Point Rate formula. In addition, community interactions were also conducted to get first-hand information from the local inhabitants. The study finds that the shoreline under study has been fluctuating. The sea advanced inland between 1972 and 2005, which is attributed mainly to intense erosion. The study further reveals that, in the past five years, the shoreline had been retreating mainly due to increased accretion. It is recommended that the shoreline under study should be monitored regularly to keep abreast with net movements that will occur in either the short term or the long term so as to factor the net effect into the management of the coastal zone.